X-ray outburst of RX J0520.5-6932, confirmed as a Be/X-ray binary - Vasilopoulos, G.; Maggi, P.; Sturm, R.; Haberl, F.; Pietsch, W.; Udalski, A.; Sasaki, M.; Immler, S. (2013)
A Swift observation performed on 2013 January 13 as part of the LMC UV survey (PI: S. Immler) detected the high-mass X-ray binary candidate RX J0520.5-6932 in a moderately bright X-ray outburst. Assuming a power-law spectrum with a photon index of 0.9 and absorption of 1021 cm-2, we derive a 0.2-12 keV flux of 1.67 × 10-12 erg s-1 cm-2. This flux is ~25 times higher than measured during a recent XMM-Newton observation (see below).
Keywords: Binary; Neutron Star; Optical; Transient; X-Ray